2010
DOI: 10.1167/iovs.09-4414
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor-1 and Cardiotrophin 1 Increase Strength and Mass of Extraocular Muscle in Juvenile Chicken

Abstract: Exogenous IGF1 and CT1 strengthen extraocular muscles during maturation. They predominantly remodel the proximal segment of juvenile extraocular muscles. This information about muscle plasticity may aid the design of pharmacologic treatment of strabismus in children during the "critical period" of oculomotor maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 35 publications
4
19
0
Order By: Relevance
“…We previously reported that IGF1 and CT1 enhance the contractile force of EOMs [11, 38]. To determine whether the speed-enhancing and force-enhancing effects among growth factors are linked or are independent from each other, we measured the contractile force after treatment of EOMs with the same growth factors in either gain-of-function or loss-of-function experiments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported that IGF1 and CT1 enhance the contractile force of EOMs [11, 38]. To determine whether the speed-enhancing and force-enhancing effects among growth factors are linked or are independent from each other, we measured the contractile force after treatment of EOMs with the same growth factors in either gain-of-function or loss-of-function experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Seventy-seven chickens and four adult Wistar rats were used in this study. Some of the same animals previously used for force analysis [38] were further examined for kinetic analysis in this study. Animals were raised in brooders or cages in ventilated rooms with constant temperature and humidity and a 12-h light/dark cycle.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although finding increased BrdU-positive cells in the satellite position in the mid region of the superior rectus muscles was somewhat surprising, similar changes in satellite cell reactivity in proximal regions of EOM after localized growth factor treatment have been reported. 27 In comparison to the effect of resection on rabbit superior rectus muscles, 12 recession surgery resulted in fewer BrdUpositive myonuclei as well as delayed upregulation compared with the rapid increase after resection surgery.…”
Section: Changes In Satellite Cells In Tenotomized and Recessed Supermentioning
confidence: 96%